1994
DOI: 10.1063/1.467853
|View full text |Cite
|
Sign up to set email alerts
|

A molecular-dynamics simulation study of the adsorption and diffusion dynamics of short n-alkanes on Pt(111)

Abstract: Using molecular-dynamics studies and static potential-energy minimization, we have resolved the mechanisms by which n-alkanes (ethane through n-decane) diffuse on a model Pt(111) surface in the low-coverage limit of a single adsorbed molecule. Our simulations reproduce all of the experimental trends seen for the adsorption and diffusion of C3–C6 on Pt(111) and Ru(001). The short alkanes (C2–C8) behave as rigid rods and their motion involves coupled translation and rotation in the surface plane. For this series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…The preferential orientation of the molecular axis in the NN direction was consistent with the molecular dynamics simulation which showed that diffusion and adsorption along the NN direction were favorable on Pt(111). 23,24 The local structure of the 2D crystals of alkanes was investigated by STM on graphite in solution; the molecular arrangement was commensurate and the angle between the molecular row and the molecular axis was 90 in both odd 20,21 and even [14][15][16][17][18][19] alkane 2D crystals on the graphite. The molecular arrangement was commensurate on graphite, Pt(111), and Cu(111) but was incommensurate on Ag-(111) and Au(111) surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferential orientation of the molecular axis in the NN direction was consistent with the molecular dynamics simulation which showed that diffusion and adsorption along the NN direction were favorable on Pt(111). 23,24 The local structure of the 2D crystals of alkanes was investigated by STM on graphite in solution; the molecular arrangement was commensurate and the angle between the molecular row and the molecular axis was 90 in both odd 20,21 and even [14][15][16][17][18][19] alkane 2D crystals on the graphite. The molecular arrangement was commensurate on graphite, Pt(111), and Cu(111) but was incommensurate on Ag-(111) and Au(111) surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the physisorption of alkanes has been studied on Au(111), 6 Pt(111), 7,8 Pt(110), 9 Ir(110), 10 Cu(100), 11 Ru(001), 12 and Cu(111), 13 under UHV conditions. However, the local arrangement of the alkanes on a metal surface has not been investigated in contrast to numerous reports of alkane adlayers on graphite at the solid/liquid interface, [14][15][16][17][18][19][20][21] although studies using molecular dynamics 12,[22][23][24][25][26][27] and infrared spectroscopy [28][29][30][31][32] under UHV conditions have been carried out after the reports by Firment and Somorjai. Furthermore, the structure of the alkane/metal interface in solution was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This is not a major problem either, however, since for long chain molecules the mismatch between the molecule and the substrate becomes so pronounced that the substrate potential felt by the chain molecule becomes less and less corrugated. 11,12,15,16 This is often the case in physisorption systems, and it has also been observed in cluster diffusion on a solid substrate. 38 The adsorption of segments of long chains is therefore delocalized, which in the present model is reflected in the fact that the lattice sites occupied by the segments do not correspond to real adsorption sites but are rather an effective representation of the chain motion on a plane.…”
Section: Model Polymer Systemmentioning
confidence: 98%
“…Molecular dynamics simulations [7][8][9]11,12,16,17 and experiments [19][20][21][22] have revealed that diffusion of short chainlike molecules can often be described by the Arrhenius description. Unfortunately, however, the actual microscopic origins of the effective activation barrier are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation